SOSIALISASI PROGRAM UNIVERSITAS BATAM KE SEKOLAH MENENGAH ATAS ( SMA) ISLAM NABILAH BATAM - Sarmini; Diana Titik; Dewi Agustina; Hendra Marta (Jurnal Pengabdian Ibnu Sina, 2022)
The high school level has announced the graduation of its students on May 5, 2022. And they are still continuing their education to a higher level, namely the Higher Education level. Knowledge related to Higher Education is very important for them to construct their future according to the preferences of each student. Therefore, the fulfillment of the needs related to Higher Education is very necessary. The socialization of the Batam University Campus Program in the context of Community Service at Nabilah Islamic High School is an activity to fulfill information obtained by high school students. It is intended that Nabilah Islamic High School students understand what and how Higher Education is. This is because according to the author's data, there are still 25% of Nabilah Islamic High School students who do not understand what Higher Education is and 54.5% are still very doubtful in understanding Higher Education. So it is very important to open the horizons of high school students before they go directly to campus.